Middlemarch - Eliot, George (New York Barnes & Noble, 1996)
It was George Eliot's ambition to create a world and portray a whole community--tradespeople, middle classes, country gentry--in the rising fictional provincial town of Middlemarch, circa 1830. Vast and crowded, rich in narrative irony and suspense, Middlemarch is richer still in character and in its sense of how individual destinies are shaped by and shape the community.
76467
Keywords: England -- Social life and customs -- Fiction -- 19th century; Young women -- Fiction -- England